Language & Culture in English as a Foreign Language Teaching: a socio-cultural experience of some exchange students from Piauí Federal Institute - Giselda dos Santos Costa (Universidade Estadual Paulista Júlio de Mesquita Filho, 2018)
The internationalization of higher education has been dramatically intensified over the last fifteen years in Brazil, creating wide-ranging opportunities as well as threats and limitations in relation to foreign language teaching practices and the teaching of culture. Many linguists and anthropologists (BYRAM, 1997; KRAMSCH, 1993; MCKAY, 2003; JENKINS, 2005) have stated that for communication to be successful the use of language must be associated with other culturally appropriated behavior, not just linguistic rules in the strict sense. In this article, we discuss the problems related to internationalization, more specifically, the discussion revolves around the sociocultural challenges faced by some students of the Federal Institute of Piauí (IFPI) regarding their experiences in the Science without Borders program spread through five countries. By using qualitative interviews, the results revealed that students had sociocultural problems which could be avoided if English teachers had worked in the language classroom before the execution of the exchange program.